Analysis Of Aceh Province Kur Bsi Financing On Increasing Income Of Small Medium Enterprise Customers - Indah Kesuma; Annisa Ilmi Faried; Dewi Mahrani Rangkuty (Yayasan Multidimensi Kreatif, 2023)
This research aims to determine and analyze the factors of people's business credit (KUR), business development, workforce, productivity, distribution, business location, selling price, length of business relevant to increasing the income of MSME customers in Aceh Province. The factors studied are people's business credit (KUR), business development, workforce, productivity, distribution, business location, selling price, length of business relevant to increasing the income of MSME customers in Aceh Province and these relevant factors have a positive and significant effect on MSME customer income. With a sample size of 253 respondents, the data was collected by distributing questionnaires and processing the data using the Confirmatory Factor Analysis (CFA) analysis method and multiple linear regression analysis methods. This research is motivated by the development of the potential of Micro, Small and Medium Enterprises (MSMEs) in Indonesia which cannot be separated from banking support in channeling financing to MSME entrepreneurs. To reduce the problems faced by MSMEs, the government is trying to issue a People's Business Credit (KUR) program. Based on the results of the Confirmatory Factor Analysis (CFA) test in the KMO and Bartlett's test tables, it shows that selling price, productivity, distribution and length of business have a significant effect on the income of MSME customers in Bener Meriah Regency, Aceh. And the results of multiple linear regression testing show that the results of partial hypothesis testing show that selling price, productivity, distribution and length of business have a significant effect on the income of MSME customers in Bener Meriah Regency, Aceh.